Taurina previne déficit na consolidação da memória em novo modelo de blackout induzido por etanol em peixe-zebra - Bertoncello, Kanandra Taisa (2019)
Intoxication and dependence caused by alcohol are among the major public health problems. Alcohol abuse can affect organs and tissues, as well as compromise physical coordination, perception, and cognition. Alcohol intoxication may lead to cognitive deficits, such as amnesia or “blackout”, an acute defect in the formation of memories resulting from a rapid increase of ethanol in the blood. Due to the negative aspects of alcohol abuse, new therapeutic strategies are needed. Thus, taurine appears as a potential target since it modulates neuronal activity, transduction signaling pathways, osmoregulation, as well as displays antioxidant properties and antagonizes glutamatergic excitotoxicity. In order to verify a potential protective effect of taurine on the cognitive deficit induced by ethanol, we used the inhibitory avoidance task. A specific shock frequency that causes significant memory retention in zebrafish, was selected. Then, we verified if ethanol concentration-dependently affects the memory and tested whether taurine pretreatments counteract ethanol-induced cognitive deficits. The inhibitory avoidance apparatus was used to investigate the potential protective effects of taurine in a new model of ethanol-induced amnesia in zebrafish. The apparatus consists of an aquarium divided into two compartments of the same size, a dark and a bright area separated by a guillotine-like partition. Three parallel metal bars are attached to each side of the dark area, connected to an electrical stimulator. Differences on the latency to enter the dark compartment were used as retention indexes. Animals subjected to an electric shock (125 mA, 3 ± 0.2 V) at 10 and 1000 Hz did not promote significant learning, while 100 Hz facilitated memory retention, which was chosen for subsequent experiments. Treatments were performed immediately after the training session. Animals were exposed to water (control), taurine (42, 150, 400 mg/L), ethanol (0.25%, 1.0% v/v) or taurine plus ethanol, to evaluate the effects on memory consolidation. Test session was performed 24 h following training. Ethanol at 0.25% did not cause cognitive deficit, but 1.0% ethanol impaired memory consolidation without altering locomotion. Posttraining administration of MK-801 elicited a similar response, suggesting that ethanol-induced amnesia may occur via inhibition of glutamatergic neurotransmission. Although taurine alone did not modulate learning, all concentrations tested prevented memory impairment. The present work proposes a new model of ethanol-induced blackout and demonstrates the protective role of taurine, reinforcing the growing utility of zebrafish to evaluate the deleterious effects of alcohol and possible therapeutic strategies.